Photoredox‐Promoted Co‐Production of Dihydroisoquinoline and H2O2 over Defective Zn3In2S6. Issue 10 (13th January 2023) - Luo, Juanjuan; Wei, Xinfa; Qiao, Yang; Wu, Chenyao; Li, Lanxin; Chen, Lisong; Shi, Jianlin
Abstract: One of the most sustainable and promising approaches for hydrogen peroxide (H2 O2 ) production in a low‐cost and environment‐friendly way is photosynthesis, which, however, suffers from poor carrier utilization and low H2 O2 productivity. The addition of proton donors such as isopropanol or ethanol can increase H2 O2 production, which, unfortunately, will inevitably elevate the entire cost while wasting the oxidizing power of holes (h + ). Herein, the tetrahydroisoquinolines (THIQs) is employed as a distinctive proton donor for the thermodynamically feasible and selective semi‐dehydrogenation reaction to highly valuable dihydroisoquinolines (DHIQs), and meanwhile, to couple with and promote H2 O2 generation in one photoredox reaction under the photocatalysis by dual‐functional Zn3 In2 S6 photocatalyst. Surprisingly, the suitably defective Zn3 In2 S6 offers an excellent and near‐stoichiometric co‐production performance of H2 O2 and DHIQs at unprecedentedly high rates of 66.4 and 62.1 mmol h ‐1 g ‐1 under visible light (λ ≥ 400 nm), respectively, which outperforms all the previously available reports even though sacrificial agents were employed in those reports. Additionally, photocatalytic redox reaction mechanism demonstrates that H2 O2 can be generated through multiple pathways, highlighting the synergistic effect among ROS (·O2 ‐ and 1 O2 ), h + and proton donor, which has been ignored in previous studies. Abstract : A dual‐functional and defective Zn3 In2 S6 photocatalyst is developed for the simultaneous efficient photocatalytic co‐syntheses of dihydroisoquinoline and H2 O2, which shows the highest rate for both reactions up to date.